Utilizing a Modified Care Coordination Measurement Tool to Capture Value for a Pediatric Outpatient Parenteral and Prolonged Oral Antibiotic Therapy Program. (17th April 2017) - Vaz, Louise E; Farnstrom, Cindi L; Felder, Kimberly K; Guzman-Cottrill, Judith; Rosenberg, Hannah; Antonelli, Richard C
Abstract: Background: Outpatient parenteral or prolonged oral antibiotic therapy (OPAT) programs reduce inpatient healthcare costs by shifting care to outpatient settings. Care coordination (CC) is a necessary component to successfully transition patients. Our objective was to assess outcomes of provider time spent on nonreimbursable CC activities in a pediatric OPAT program. Methods: We used a qualitative feasibility pilot design and modified the Care Coordination Measurement Tool. We captured nonreimbursable CC activity and associated outcome(s) among pediatric patients enrolled in OPAT from March 1 to April 30, 2015 (44 work days) at Doernbecher Children's Hospital. We generated summary statistics for this institutional review board-waived QI project. Results: There were 154 nonreimbursable CC encounters conducted by 2 infectious diseases (ID) providers for 29 patients, ages 17 months–15 years, with complex infections. Total estimated time spent on CC was 54 hours, equivalent to at least 6 workdays. Five patients with complex social issues used 37% of total CC time. Of 129 phone events, 38% involved direct contact with families, pharmacies (13%), primary care providers (13%), and home health nursing (11%). Care coordination prevented 10 emergency room (ER) visits and 2 readmissions. Care coordination led to 16 additional, not previously scheduled subspecialist and 13 primary care visits. The OPAT providers billed for 32 clinic visits during the study period. Conclusions: Nonreimbursable CC work by OPAT providers prevented readmissions and ER visits and helped facilitate appropriate healthcare use. The value of pediatric OPAT involvement in patient care would have been underestimated based on reimbursable ID consultations and clinic visits alone.